Group Counselling of Underachievers - Altman, Harold A.; Conklin, Rodney C.; Hughes, Ronald C. (Canadian Journal of Counselling and Psychotherapy, 1972)
Grade 9 underachieving volunteers and non-volunteers were taught effective study skills through group reinforcement counselling. Direct and statistical controls were emphasized in the analysis. Results supported reinforcement counselling with volunteering clients. There was improved achievement of non-counselled non-volunteers who received a "study guide."